Impact of extracorporeal membrane oxygenation in immunocompetent children with severe adenovirus pneumonia - Tingting Shi; Chen Chen; Huifeng Fan; Minghua Yu; Ming Li; Diyuan Yang; Li Huang; Zhiqiang Nie; Gen Lu (BMC Pulmonary Medicine, 2023)
Abstract Background Severe adenovirus (Adv.) pneumonia can cause significant mortality in young children. There has been no worldwide consensus on the impact of extracorporeal membrane oxygenation (ECMO) in immunocompetent children with severe Adv. pneumonia. This study aimed to assess the impact of ECMO in immunocompetent children with severe Adv. pneumonia. Methods This study evaluated the medical records of 168 hospitalized children with severe Adv. pneumonia at the Guangzhou Women and Children’s Medical Center between 2019 and 2020.Nineteen patients in the ECMO group and 149 patients in the non-ECMO group were enrolled. Results Between these two groups, there were no differences in host factors such as sex, age (all P > 0.05). Significant differences were observed in shortness of breath/increased work of breathing; cyanosis; seizures; tachycardia; the partial pressure of oxygen in arterial blood (PO2); the ratio of PaO2 to the fraction concentration of oxygen in inspired air (FiO2; P/F); white blood cell, lymphocyte, monocytes, lactate dehydrogenase (LDH), serum albumin, and procalcitonin levels; and, pulmonary consolidation (all P < 0.05). There were significant differences in the parameters of mechanical ventilation (MV) therapy and complications such as respiratory failure, acute respiratory distress syndrome, septic shock, length of hospitalization, and death (all P < 0.05). The maximum axillary temperatures, respiratory rates, heart rates and LDH levels after receiving ECMO were significantly lower than those before ECMO (all P < 0.05). Additionally, SPO2, PO2, and P/F were significantly higher than those before ECMO (all P < 0.05). In MV therapy, FiO2, PIP, and PEEP were significantly lower than those before ECMO (all P < 0.05). Conclusions In our study, the clinical conditions of the patients in the ECMO group were much more severe than those in the non-ECMO group. Our study showed that ECMO might be beneficial for the patients with severe Adv. pneumonia.